2015
DOI: 10.1142/s0218301315501013
|View full text |Cite
|
Sign up to set email alerts
|

De-confinement in small systems: Clustering of color sources in high multiplicity p̄p collisions at s = 1.8TeV

Abstract: It is shown that de-confinement can be achieved in high multiplicity non jetpp collisions at √ s= 1.8 TeV Fermi National Accelerator Laboratory(FNAL-E735) experiment. Previously the evidence for deconfinement was the demonstrated by the constant freeze out energy density in high multiplicity events. In this paper we use the same data but analyze the transverse momentum spectrum in the framework of the clustering of color sources. The charged particle pseudorapidities densities in the range 7.0 ≤ dN c /dη ≤26.0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 46 publications
0
32
0
Order By: Relevance
“…7, but it shows the de-pendences of initial temperature (a)(c) T i1 and (b)(d) T i2 on (a)(b) m 0 and (c)(d) C, where T i1 (T i2 ) is obtained by the root-mean-square p T divided by √ 2, i.e. p 2 T 1 /2 ( p 2 T 2 /2) according to [37,38,39]. The symbols represent the results obtained from the fitting functions (Eqs.…”
Section: Resultsmentioning
confidence: 99%
“…7, but it shows the de-pendences of initial temperature (a)(c) T i1 and (b)(d) T i2 on (a)(b) m 0 and (c)(d) C, where T i1 (T i2 ) is obtained by the root-mean-square p T divided by √ 2, i.e. p 2 T 1 /2 ( p 2 T 2 /2) according to [37,38,39]. The symbols represent the results obtained from the fitting functions (Eqs.…”
Section: Resultsmentioning
confidence: 99%
“…According to refs. [37][38][39], if the initial temperature ( i T ) of the interacting system is approximately described by 2…”
Section: Resultsmentioning
confidence: 99%
“…The decreasing trend of F (ξ) is due to the production of high string density, which reveals more suppression of color charges in comparison to lower collisions energies and centralities. F (ξ) in heavy-ion collisions is presented as a function of dN ch /dη scaled with the transverse overlap area S N , which are estimated by using the Glauber model [11] along with the results in highmultiplicity non-jet pp collisions at √ s = 1.8 TeV from FNAL (Fermi National Accelerator Laboratory) E735 experiment [23] in figure 3. It is observed that F (ξ) falls onto a universal scaling curve for hadron-hadron and nucleus-nucleus collisions.…”
Section: Resultsmentioning
confidence: 99%